2020
DOI: 10.1073/pnas.1915386117
|View full text |Cite
|
Sign up to set email alerts
|

STIM2 targets Orai1/STIM1 to the AKAP79 signaling complex and confers coupling of Ca 2+ entry with NFAT1 activation

Abstract: The Orai1 channel is regulated by stromal interaction molecules STIM1 and STIM2 within endoplasmic reticulum (ER)-plasma membrane (PM) contact sites. Ca2+signals generated by Orai1 activate Ca2+-dependent gene expression. When compared with STIM1, STIM2 is a weak activator of Orai1, but it has been suggested to have a unique role in nuclear factor of activated T cells 1 (NFAT1) activation triggered by Orai1-mediated Ca2+entry. In this study, we examined the contribution of STIM2 in NFAT1 activation. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…We recently revealed that both endogenous STIM1 and STIM2 have major contributions to SOCE in the colorectal cancer cell line HCT116 ( Emrich et al, 2019 ). Recent studies proposed that STIM2 enhances Ca 2+ signals by recruiting STIM1 to Orai1 channels under conditions of modest store depletion ( Ong et al, 2015 ; Son et al, 2020 ; Subedi et al, 2018 ), in agreement with our findings. Whether STIM1/2 function as homodimers or heterodimers requires further investigations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We recently revealed that both endogenous STIM1 and STIM2 have major contributions to SOCE in the colorectal cancer cell line HCT116 ( Emrich et al, 2019 ). Recent studies proposed that STIM2 enhances Ca 2+ signals by recruiting STIM1 to Orai1 channels under conditions of modest store depletion ( Ong et al, 2015 ; Son et al, 2020 ; Subedi et al, 2018 ), in agreement with our findings. Whether STIM1/2 function as homodimers or heterodimers requires further investigations.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier reports suggested that STIM1 is solely required for Ca 2+ oscillations ( Bird et al, 2009 ; Wedel et al, 2007 ), while more recent studies suggested that STIM2 is the key regulator of Ca 2+ oscillations ( Ong et al, 2015 ; Thiel et al, 2013 ). Further complicating this picture, evidence has emerged that STIM2 actively recruits STIM1 to ER-PM junctions under conditions of modest ER Ca 2+ depletion ( Ong et al, 2015 ; Son et al, 2020 ; Subedi et al, 2018 ), highlighting the complex function of STIM1/2 in Ca 2+ signaling.…”
Section: Introductionmentioning
confidence: 99%
“…We recently revealed that coordination between endogenous STIM1 and STIM2 plays a critical role in mediating SOCE in the colorectal cancer cell line HCT116 40 . Further, recent studies presented evidence that STIM2 can serve as an enhancer of receptor-activated Ca 2+ signaling by recruiting STIM1 to Orai1 channels under conditions of modest store depletion 33,37,38 , in agreement with our findings. Whether STIM1 and STIM2 function as homodimers or heterodimers is an important question that requires further investigations.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, other studies suggested that STIM2 is the key regulator of Ca 2+ oscillations 33,34 . Further complicating this picture, evidence has emerged that STIM2 actively recruits STIM1 to ER-PM junctions under conditions of modest ER Ca 2+ depletion 33,37,38 , suggesting that STIM1/2 play a dynamic and cooperative role in Ca 2+ signaling than previously appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…STIM1 is also more efficient in generating large ORAI-mediated Ca 2+ signals in comparison to STIM2 (Wang et al, 2014). STIM2 has recently been reported to facilitate the coupling of ORAI1 function with nuclear factor of activated T-cells 1 (NFAT1) activation (Son et al, 2020). Moreover, STIM2 has been identified as an important regulator of cell physiology and pathology, particularly in immune cells, neuronal cells, and other cells originating from the neural crest, such as melanocytes and melanoma (Berna-Erro et al, 2009Cheng et al, 2012;Clemens et al, 2017;Diercks et al, 2018;Shaw et al, 2014;Stanisz et al, 2012Stanisz et al, , 2014Sun et al, 2014;Yoshikawa et al, 2019).…”
Section: Introduction Soce and Crac Channelsmentioning
confidence: 99%